Naïn ou Naïm (Lc 7.11): une différence révélatrice - Lovinfosse, Marie de (New Testament studies, 2018)
This study investigates spelling variants of the name of the city where Jesus raises the only son of a widow, in Lk 7.11: Nain or Naim. The study develops along three lines: textual critic, Hebraic etymology, ancient geography. The investigation eventually raises the question of the theological significance of the miracle of Nain.